Dual-functional light-emitting perovskite solar cells enabled by soft-covered annealing process. (July 2019) - Liu, Yanliang; Hangoma, Pesi Mwitumwa; Tamilavan, Vellaiappillai; Shin, Insoo; Hwang, In-Wook; Jung, Yun Kyung; Lee, Bo Ram; Jeong, Jung Hyun; Park, Sung Heum; Kim, Kwang Ho
Abstract: Solution-processable perovskite semiconductors have demonstrated excellent performance in both perovskite solar cells (PeSCs) and perovskite light emitting diodes (PeLEDs). Their low exciton binding energy and excellent charge transport properties allow the conversion of photons into free electrons and holes and vice versa with minimal energy loss. In addition, planar PeSCs and PeLEDs have similar device architecture. These aspects inspired us to fabricate a dual-functional device with both SC and LED functions, here termed a light-emitting perovskite solar cells (LEPeSCs). However, the absence of an effective fabrication method to control grain size, uniformity, grain boundaries, and coverage of perovskite film inevitably limits device performance of dual-functional LEPeSCs. Here, we have demonstrated an efficient dual-functional LEPeSCs with planar device configuration of ITO/PEDOT:PSS/CH3 NH3 PbBrI2 /PC61 BM/Ca/Al, which is able to reversibly convert luminous energy to electric energy or electric energy to luminous energy in a single device. By developing a new soft-covered annealing method, we obtained optimized grain morphology with large grain size, high uniformity, and decreased grain boundaries, which is difficult to achieve with conventional fabrication methods. The LEPeSCs exhibits high performance in both PeSCs and PeLEDs modes, with power conversion efficiency of 14.02% in SC mode and bright red-light emission of 1710 cd/cm 2 at 4 V in LED mode. Graphical abstract: Efficient dual-functional light-emitting perovskite solar cells (LEPeSCs) have been demonstrated by using a new soft-covered annealing method. The LEPeSCs exhibits high performance in both solar cell (SC) and light emitting diode (LED) modes, with power conversion efficiency of 14.02% in SC mode and bright red-light emission of 1710 cd/cm2 at 4 V in LED mode. Image 1 Highlights: Dual-functional light-emitting perovskite solar cells was fabricated. New soft-covered annealing method was developed for making CH3 NH3 PbBrI2 film. Large-grained flat and dense CH3 NH3 PbBrI2 film was achieved. High-quality CH3 NH3 PbBrI2 film is crucial for efficient LEPeSCs.